Resource allocation for coexistence of eMBB and bursty URLLC based on queueing with preemption - Wei Guo; Kai Liang; Yuewen Song; Xiaoli Chu; Gan Zheng; Kai-Kit Wong (Journal of Information and Intelligence, 2025)
Enhanced mobile broadband (eMBB) and ultra-reliable low-latency communication (URLLC) are two critical services in 5G mobile networks. While there has been extensive research on their coexistence, few studies have considered the impact of bursty URLLC on their coexistence performance. In this paper, we propose a method to allocate computing and radio resources for coexisting eMBB and bursty URLLC services by preempting both computing queues in the base station (BS) and time-frequency resources at the air interface. Specifically, we first divide the computing resources at the BS into a shared part for both URLLC and eMBB users and an exclusive part only for eMBB users, and propose a queuing mechanism with preemptive-resume priority for accessing the shared computing resources. Furthermore, we propose a preemptive puncturing method and a threshold-based queuing mechanism in the air interface to enable the multiplexing of eMBB and URLLC on shared time-frequency resources. We analytically derive the average queuing delay, average computation delay, and average transmission delay of eMBB and URLLC packets. Based on this analysis, we formulate a mixed-integer nonlinear programming problem to minimize the average delay of URLLC packets while satisfying the average delay and throughput requirements of eMBB by jointly optimizing the eMBB subcarrier allocation, the URLLC subcarrier scheduling and the computing resource allocation. We decompose this problem into three sub-problems and solve them alternately using a block coordinate descent algorithm. Numerical results show that our proposed method reduces the outage probability and average delay of URLLC compared to the existing works.